Karakteristik Bahasa Slang di Kolom Komentar Akun Tiktok @imeyhou - Silvy Banetri; Siti Ainim Liusti (Persona: Kajian Bahasa dan Sastra, 2023)
This study aims to (1) describe the form of the slang lexicon found in the comments column of the Tiktok @imeyhou account. 2) Describe the process of forming a slang lexicon in the comments column of the @imeyhou Tiktok account. (3) Describe the meaning of the slang lexicon in the comments column of the @imeyhou Tiktok account. This research is a qualitative research using descriptive method. The results found first, based on the results of the study found 105 data that included slang. Based on the form, in this study found slang lexicons in the form of monomorphemic and polymorphemic forms. However, the most dominant of the two forms is the slang lexicon of monomorphemic forms, such as kiut, lusyu, receh, seterong, kicil, and priti. Second, based on the formation process in this study, four types of slang lexicon formation processes were found, namely (1) affixation, (2) reduplication, and (3) acronymization. The most dominant process of forming a slang lexicon is the process of acronym or shortening of words, for example betewe, kyk, gtg, ytta, insc, dan omegot. Third, based on the meaning of the slang lexicon, lexical and grammatical meanings are found.